Gender categories seen by university students in the School of Nursing at the University of Cádiz - Lázaro González Calvo; Álvaro Bernalte Benazet (Universidad de Alicante, 2012)
Objective. Our aim has been closer to the vision of young people about the current meanings of masculine and feminine, defined as objects of study to final year university nursing. Methodology. Our position is qualitative ontologically and epistemologically constructivist, using techniques: participant observation, the nominal group technique and focus group techniques. Results. The results are that the current female profile is based on the following terms: independent, feisty, single, self, and emotional and men as follows: honest, hardworking, strong, sensitive, and tolerant. Conclusions. Among the findings could point out that men and women who seemed to be simply human beings in their conversations, do not agree on any ITEM descriptive of the masculine and feminine words are different than they were previously mentioned stereotypes, but still do not agree no point profiles.